KEBIJAKAN POLITIK TAWAN KARANG PADA MASA KERAJAAN BALI KUNO DAN KOLONIAL BELANDA - Suwindiatrini, Komang Ayu (Humanis; Volume 9. No. 1. Oktober 2014)
Tawan karang was more often associated with the Dutch colonial period, actually has appeared since ancient Bali period. The appearance of the tawan karang during the captivity of ancient Bali can be found on the inscription such as Sembiran AI and Bebetin AI. In the time of ancient Bali , tawan karang was used to keep land area through the water’s territory of the enemy's attack in the form of a government policy. While the Dutch colonial period , tawan karang was not just a political policies as efforts to protect themselves, but also as a form of resistance and maintaining cultural traditions that have been passed down .The problem to be solved in this research about the function and role of political policy during the reign of tawan karang on ancient Bali and Dutch Colonial period. The theory for this study are theory of power relations and hegemony. This qualitative study uses data collection methods such as literature research, documentation and observation. The results obtained about function of tawan karang from political perspective of ancient Bali was an effort the entire royal elements to keep the existence of external threats and attacks. During the Dutch colonial, function and the role of tawan karang were progress to preserve life and fight for the truth. In the Dutch colonial period, the kingdoms in Bali and the Government of the Netherlands use tawan karang as one of another way to launch tactics that embodied in a political policy .
Keywords: tawan karang, ancient Bali, Dutch colonial